The Effect of Black Garlic in Lowering Blood Pressure in Hypertension Patients at Jayamekar Health Center, West Bandung Regency - Rumaseuw, Ellen Stephanie; Saptiningsih, Monica; Raniadita, Maria Alfa (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
The Prolanis program may be a wellbeing benefit framework with a proactive community-based approach that specifically includes hypertension and diabetes patients through community strengthening to decrease NCDs in an coordinates way. Based on the comes about of the 2018 Basic Health Survey, the illnesses most commonly endured by the elderly are hypertention (63.5%), dental issues (53.6%), joint problems (18%), and mouth problems (17%), diabetes (5.7%), heart attack (4.5%) and stroke (4.4%), kidney (0.8%), and cancer (0.4%). The definition of hypertension according to the American Health Association (AHA) is a condition of increased blood pressure, characterized by blood pressure values greater than 130/90 mmHg when measured manually or digitally. Garlic (Allium sativum L.), a plant that is used extensively in the culinary and medical industries, is one of the natural remedies for high blood pressure. Fermentation is one way to turn garlic into black garlic. This study employed a paired sample t-test dependent test for data analysis and a pre-experimental design with a single group pretest and posttest design without a comparison group. After giving two bulbs of single black garlic per day for a week, the study's average posttest systolic blood pressure was 138.31, with a P-value of 0.008. Single black garlic has an effect on reducing blood pressure in hypertensive participants at Jayamekar Health Center, West Bandung Regency.